Improving Performance Services for Customer Satisfaction: A Case Study of Kentucky Fried Chicken - Lew, Tek Yew; Paul, Gadi Dung; Azmi, Nurul Atikah Binti; Suimi, Nursyahidah Binti Ahmad; Azhar, Nurul Hanisah Binti; Rozaidi, Nurul Irdina Binti; Indrastata, Daiva Fifqi; Maulana, Erika (AIBPM Publisher, 2023)
From 2020 to 2021, many KFC outlets are going into liquidation, because the companyhas suffered losses to the point where they cannot pay their obligations. Apart from the impact of the pandemic, the increasing number of competitors in the fast-food sector is also the cause of the decline in KFC's business. To survive, KFC must have service performance that can increase customer satisfaction, so that customers continue to choose KFC as a place to fulfill their desires. KFC in Sungai Dua, Gelugor, Penang is the subject of this investigation. In conclusion, this study aims to examine customer satisfaction, happiness towards ambiance of perceived price, food quality, service quality, and physical environment quality, also to examine related services designed to meet customer needs. The atmosphere of the facilities, quality of service, quality of food, are important efforts to meet all the needs and desires of consumers and meet consumer expectations so that their business can continue to run and survive among its competitors. For KFC companies, we can find out the problems they have by using a survey method through questionnaires distributed to KFC customers which contain their satisfaction with service performance at KFC and what are the shortcomings that need to be improved from the services provided.